2016
DOI: 10.7708/ijtte.2016.6(3).06
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Level-of-Service on Urban Arterials: A Case Study in Kolkata Metropolis

Abstract: Mixed traffic conditions in emerging countries like India make it difficult to adopt Level of Service (LOS) criteria given in Highway Capacity Manual (HCM) of developed nations. Present study aims at identifying alternative performance measure which will exhibit better compatibility to define LOS in context of urban mixed traffic. A total sixteen hours of traffic volume and speed data have been recorded by videography at selected road segment of a six lane divided urban arterial in Kolkata metropolis. Percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…On the other hand, our results show that most environments in which the relative exposure of female drivers is higher are a priori related to a lower risk of crash-related fatalities or severe injuries (e.g., urban areas, daytime, good light conditions, weekdays, or good infrastructure) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Accordingly, several previous studies have found a higher degree of self-regulation (i.e., restricting driving exposure to avoid risky driving circumstances) in women, especially among older ones, perhaps due to less driving experience and self-confidence or higher driving-related anxiety [ 34 , 35 , 39 , 44 ].…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, our results show that most environments in which the relative exposure of female drivers is higher are a priori related to a lower risk of crash-related fatalities or severe injuries (e.g., urban areas, daytime, good light conditions, weekdays, or good infrastructure) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Accordingly, several previous studies have found a higher degree of self-regulation (i.e., restricting driving exposure to avoid risky driving circumstances) in women, especially among older ones, perhaps due to less driving experience and self-confidence or higher driving-related anxiety [ 34 , 35 , 39 , 44 ].…”
Section: Discussionmentioning
confidence: 86%
“…Biswas et al [15] conducted field investigations in Kolkata metropolis city, utilizing a video graphic approach to observe and collect traffic flow characteristics on urban arterials. The obtained data, such as mean speed, standard deviation, and coefficient of variation, have been paired with standard values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the values of K 3 in Table 4 depend on the typical observed traffic fluidity and the number of daylight hours with congested traffic flow. The term "congested flow" complies with the methodology proposed by [45] to evaluate the level of service of an urban arterial: this condition occurs when the percentage speed reduction from free flow speed appears greater than 50%. The hazardousness factor K 4i depends on the expected fatality induced by the defect i on vulnerable road users.…”
Section: Users Observed Condition Traffic Flow Condition Code K 2 Valuesmentioning
confidence: 99%